PENGALAMAN BULLYING DALAM TINJAUAN AKTIVITAS KEHIDUPAN SEKOLAH DI SDN DESA TANJUNG LUAR - Julia Urba Swastika (Indonesian Society and Religion Research, 2024)
This research was motivated by the attention of researchers about the rampant cases of bullying that occur at the elementary school level. This research is a type of survey research with a quantitative approach that aims to explore variables or indicators of bullying experiences that occur in elementary school life in Tanjung Luar Village, Keruak District, East Lombok Regency. The population in this study is all students of Tanjung Luar State Elementary School, Keruak District, East Lombok Regency in 2023/2024 totaling 1,068 people with a total sample of 168 people, each of which 56 people were taken from each school. Data will be collected through questionnaires specifically designed to identify students' bullying experiences. The results of this study showed the level of bullying experience at Tanjung Luar 1 State Elementary School at 38.2%, Tanjung Luar 2 State Elementary School at 46.6%, and Tanjung Luar 3 State Elementary School at 45.95%. While the level of bullying experience in the review of school life activities at State Elementary School Tanjung Luar Village itself was relatively low at 44,9%, this was according to the Guttman scale percentage table, as well as bullying experiences in the review of school life activities at Tanjung Luar State Elementary School which had the most cases of verbal bullying at 19.08%. The findings of this study are expected to provide a deeper understanding of the problem of bullying in the elementary school environment, provide recommendations for improvements in school policies, as well as become the basis for the development of more effective bullying prevention programs in the future. This research will not only contribute to the academic understanding of bullying at the elementary level but also provide practical insights that can improve the safety and well-being of students at State Elementary School Tanjung Luar Village.